Buprenorphine for Opioid Use Disorder in the Emergency Department: A Retrospective Chart Review - Kathy T. LeSaint; Brent Klapthor; Ralph C. Wang; Curtis Geier (Western Journal of Emergency Medicine, 2020)
Introduction: Emergency care providers routinely treat patients with acute presentations and sequelae of opioid use disorder. An emergency physician and pharmacist implemented a protocol using buprenorphine for the treatment of patients with opioid withdrawal at an academic, Level I trauma center. We describe our experience regarding buprenorphine implementation in the emergency department (ED), characteristics of patients who received buprenorphine, and rates of outpatient follow-up. Methods: We conducted a retrospective chart review of all patients in the ED for whom buprenorphine was administered to treat opioid withdrawal during an 18-month period from January 30, 2017–July 31, 2018. Data extraction of a priori-defined variables was recorded. We used descriptive statistics to characterize the cohort of patients. Results: A total of 77 patients were included for analysis. Thirty-three patients (43%) who received buprenorphine did not present with the chief complaint of opioid withdrawal. Most patients (74%) who received buprenorphine last used heroin, and presented in moderate opioid withdrawal. One case of precipitated withdrawal occurred after buprenorphine administration. Twenty-three (30%) patients received outpatient follow-up. Conclusions: This study underscores the safety of ED-initiated buprenorphine and that buprenorphine administration in the ED is feasible and effective.